Novel PV Array Reconfiguration and Integration with a Maximum Power Point Tracking Algorithm: RMPPT - Güngör, Okan; Kahveci, Hakan (Arabian journal for science and engineering (2011), 2023)
Partial shading significantly impacts the output power of photovoltaic (PV) arrays. This issue can be addressed by reconfiguring connections or positions of modules within the PV array. However, reconfiguration approaches present some drawbacks including the requirements of manual effort, complex algorithms, difficulty in implementation, and switching matrices that increase power losses. To overcome these issues, we present a low-cost and easily implemented reconfiguration method with integration into a maximum power point tracking (MPPT) algorithm for a PV array. We denote our MPPT approach as reconfigurable MPPT (RMPPT), and verify its applicability using a particle swarm optimization (PSO) algorithm, namely the reconfigurable PSO. Consequently, this approach has enhanced the output power of the PV array by at least 7.2% compared to PNO (perturb and observe) and PSO-based MPPT under realistic weather conditions.